2023
DOI: 10.1037/vio0000421
|View full text |Cite
|
Sign up to set email alerts
|

Types, subtypes, and clinical correlates of peer victimization in college: A system science perspective.

Abstract: Objective: Types and subtypes of peer victimization (PV) behaviors have long been identified among school-age children and adolescents. The present study aims to establish such typologies for older adolescents and young adults who are still in school given the fact that colleges and universities are increasingly concerned about such behaviors among their students. Method: The present study develops a PV typology for college students via network psychometrics. Through Qualtrics Panels, a nationwide sample of 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Our prediction that greater in-person and online victimization would independently predict greater amounts of depressive symptoms was supported. Our findings are in concert with and further contribute to prior research establishing links between in-person victimization and negative outcomes such as substance use, criminal behavior, loneliness, and avoidance (Agnew, 1992;Klomek et al, 2008;Kochenderfer & Ladd, 1996;Liu et al, 2023;Mitchell et al, 2007). Adding to prior literature (Mitchell et al, 2007), we also found more online victimization was associated with greater depressive symptoms.…”
Section: Victimization and Depressive Symptomssupporting
confidence: 85%
See 3 more Smart Citations
“…Our prediction that greater in-person and online victimization would independently predict greater amounts of depressive symptoms was supported. Our findings are in concert with and further contribute to prior research establishing links between in-person victimization and negative outcomes such as substance use, criminal behavior, loneliness, and avoidance (Agnew, 1992;Klomek et al, 2008;Kochenderfer & Ladd, 1996;Liu et al, 2023;Mitchell et al, 2007). Adding to prior literature (Mitchell et al, 2007), we also found more online victimization was associated with greater depressive symptoms.…”
Section: Victimization and Depressive Symptomssupporting
confidence: 85%
“…Additionally, young adults may face other unique stressors like balancing their academics (if in college), social life, and financial independence, or lack thereof. This theoretical perspective is supported by empirical findings as well; in-person victimization has been linked to the negative mental health outcomes in children and older youth samples, including higher levels of depressive symptoms, loneliness, school avoidance, poor academic performance, and substance use (Klomek et al, 2008;Kochenderfer & Ladd, 1996;Liu et al, 2023;Mitchell et al, 2007).…”
Section: Theoretical Framingmentioning
confidence: 72%
See 2 more Smart Citations
“…Regarding stress, a study by Liu et al (2022) revealed that relational peer victimization and abusive peer victimization were found to be associated with self-reported depression and stress. Additionally, Dahlen et al (2013) found that relational aggression and victimization were associated with increased levels of stress as well as other maladaptive outcomes such as depression, anxiety, anger and alcohol problems.…”
Section: Peer Victimization and Stressmentioning
confidence: 99%